Keterkaitan Pengalaman dan Kepuasan Terhadap Minat Berkunjung Kembali di Lawang Sewu Semarang - Nico Surya Ardana; Andhika Djalu Sembada; Deni Dwi Ananti (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
This study aims to determine and analyze the relationship between visitor experience and visitor satisfaction with tourist revisit interest in Lawang Sewu. Data collection techniques through observation, literature study and questionnaire distribution. For data analysis techniques using validity and reliability tests, then hypothesis testing using the spearman rank correlation test. The results of the analysis found that visitor experience has a significant relationship with a relationship that is categorized as strong because it has a correlation corefficient value of 0.589 and has a positive direction of relationship with tourist revisit interest. Then visitor satisfaction has a significant relationship as well with a relationship that is categorized as strong because it has a correlation corefficient value of 0.742 and has a positive direction of relationship with tourist revisit interest in Lawang Sewu.